Persepsi Wajib Pajak Orang Pribadi terhadap Penerapan Coretax Administration System (CTAS) dalam Optimalisasi Penerimaan Pajak di KPP Pratama Makassar Selatan - Idris, Hariany; Sangkala, Masnawaty; Rahman, Ahmad Nashiruddin Mushoddiq; Ginting, Chris Dayanti Br (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2025)
This study aims to examine the perceptions of individual taxpayers regarding the implementation of the Coretax Administration System (CTAS) in optimizing tax revenue at the South Makassar Tax Office (KPP). This study focuses on taxpayer digital literacy and tax compliance costs, both partially and simultaneously, as well as their influence on tax revenue optimization. The research sample consisted of 100 individual taxpayers registered at the South Makassar Tax Office, selected using purposive sampling. Data were collected through documentation and analyzed using classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results show that taxpayers' digital literacy has a significant positive effect on tax revenue optimization, indicating that the better taxpayers' digital understanding, the higher their compliance in tax reporting, which supports tax revenue optimization. In addition, tax compliance costs also have a positive effect on tax revenue, with lower compliance costs increasing the likelihood of tax revenue optimization. Overall, this study shows that both variables have a significant contribution to tax revenue optimization efforts.